The Challenges and Rewards of Running a Geospace Environment Modeling Challenge - Hietala H.; Dimmock A. P.; Zou Y.; Garcia-Sage K. (AMER GEOPHYSICAL UNION, 2025)
Geospace Environment Modeling (GEM) is a community-driven, National Science Foundation-sponsored research program investigating the physics of the Earth's magnetosphere and its coupling to the solar wind and the atmosphere. This commentary provides an introduction to a Special Issue collating recent studies related to a GEM Challenge on kinetic plasma processes in the dayside magnetosphere during southward interplanetary magnetic field conditions. We also recount our experiences of organizing such a collaborative activity, where modelers and observers compare their results, that is, of the human side of bringing researchers together. We give suggestions on planning, managing, funding, and documenting these activities, which provide valuable opportunities to advance the field.Plain Language Summary Geospace Environment Modeling (GEM) is a community-driven, National Science Foundation-sponsored research program investigating the physics of the Earth's magnetosphere and its coupling to the solar wind and the atmosphere. An integral part of the program is the so-called "Challenges", which bring people together to compare models and observations in order to advance our understanding of the near-Earth space environment. This commentary provides an introduction to a Special Issue collating recent studies related to one such collaborative effort. We also share our experiences as early-career scientists organizing such an activity, to aid those who might take part in such endeavors in the future. We give suggestions on planning, managing, funding, and documenting the activities.